Printed titanium implants in UK craniomaxillofacial surgery. Part II: perceived performance (outcomes, logistics, and costs). Issue 3 (April 2021) - Goodson, A.M.C.; Parmar, S.; Ganesh, S.; Zakai, D.; Shafi, A.; Wicks, C.; O'Connor, R.; Yeung, E.; Khalid, F.; Tahim, A.; Gowrishankar, S.; Hills, A.; et al.
Abstract: This second part explores perceptions and understanding of clinical performance, turnaround, and costs for printed titanium implants or plates in common procedures, evaluating both 'in-house' and 'outsourced' CAD-CAM pathways. A cross-sectional study, supported by the British Association of Oral and Maxillofacial Surgeons (BAOMS) and a national trainee-led recruitment team, was conducted over 14 weeks. A total of 132 participants took part (demographic data is reported in Part I). For fibular-flap mandibular reconstruction, most participants (69% - 91%) perceived printed titanium as superior to intraoperatively or preoperatively hand-bent plates for surgical duration, accuracy, dental restorability, and aesthetics. There was less agreement about complications and plate-failure risks. Most perceived printed plates to be superior to traditional wafer-based maxillary osteotomy for surgical duration (61%) and maxillary positioning (60%). For orbital floor repair, most perceived improvements in surgical duration (83%, especially higher-volume operators p=0.009), precision (84%), and ease of placement (69%). Rarely (less than 5%) was any outcome rated inferior to traditional techniques for any procedure. Perceived turnaround times and costs were variable, but the greatest consensus was for two-segment fibular-flap reconstructions and orbital floor repair. Industry estimates were generally consistent between two company representatives, but manufacturing-only costs differed when using in-house (departmental) designers. Costs and turnaround times are questionable barriers since few understand 'real-world' figures. Designing in-house can dramatically alter costs. Improved accuracy and surgical duration are common themes but biomechanical benefits are less-well understood. This study paints a picture of the potentially routine applications and benefits of printed titanium, capacity for uptake, understanding amongst surgeons, and areas for improvement.